Auditoria financiera a la Corporación Municipal de Cultura y Turismo de la ciudad de Armenia para la vigencia fiscal 2011 (2012)
For the development of the audit to La Corporación Municipal de Cultura y Turismo de Armenia were analyzed the financial statements up to december 31 2011. In order to give them a dictum of reasonableness, was studied the general knowledge of the audited entity, and then was created an analysis which helped to the obtention of truthful information given in the SIA (Sistema Integrado de Auditoria).